Waste Paper as a Valuable Resource: An Overview of Recent Trends in the Polymeric Composites Field - de Oliveira, Daniel Magalhães [UNESP]; de Bomfim, Anne Shayene Campos [UNESP]; Benini, Kelly Cristina Coelho de Carvalho [UNESP]; Cioffi, Maria Odila Hilário [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Rodrigue, Denis (MDPI, 2023)
This review focuses on polymeric waste-paper composites, including state-of-the-art analysis with quantitative and qualitative discussions. Waste paper is a valuable cellulose-rich material, produced mainly from office paper, newspaper, and paper sludge, which can be recycled and returned to paper production or used in a new life cycle. A systematic literature review found 75 publications on this material over the last 27 years, with half of those published during the last five years. These data represent an increasing trend in the number of publications and citations that have shown an interest in this field. Most of them investigated the physicomechanical properties of composites using different contents of raw waste paper or the treated, modified, and cellulose-extracted types. The results show that polyethylene and polypropylene are the most used matrices, but polylactic acid, a biodegradable/sourced polymer, has the most citations. The scientific relevance of waste-paper composites as a subject includes the increasing trend of the number of publications and citations over the years, as well as the gaps identified by keyword mapping and the qualitative discussion of the papers. Therefore, biopolymers and biobased polymers could be investigated more, as well as novel applications. The environmental impact in terms of stability and degradation should also receive more attention regarding sustainability and life cycle analyses.
Keywords: composite; mechanical properties; polymer; recycling; waste paper